Blood pressure variability and its association with echocardiographic parameters in hypertensive diabetic patients. Issue 1 (December 2016) - Massierer, Daniela; Leiria, Liana; Severo, Mateus; Ledur, Priscila; Becker, Alexandre; Aguiar, Fernanda; Lima, Eliandra; Freitas, Valéria; Schaan, Beatriz; Gus, Miguel
Abstract Background Blood pressure (BP) variability is associated with target organ damage in hypertension and diabetes. The 24 h ambulatory blood pressure monitoring (24 h-ABPM) has been proposed as an evaluation for BP variability using several indexes [standard deviation (SD) of mean BP, coefficient of variation (CV), BP variation over time (time-rate index)]. Methods We evaluated the association between BP variability measured by 24 h-ABPM indexes and echocardiographic variables in a cross-sectional study in 305 diabetic-hypertensive patients. Results Two groups were defined by the median (0.55 mmHg/min) of time-rate systolic BP (SBP) index and classified as low or high variability. Age was 57.3 ± 6.2 years, 196 (64.3 %) were female. Diabetes duration was 10.0 (5.0–16.2) years, HbA1c was 8.2 ± 1.9 %. Baseline clinical characteristics were similar between low (n  = 148) and high (n  = 157) variability groups. Office SBP and systolic 24 h-ABPM were higher in the high variability group (139.9 mmHgvs 146.0 mmHg, P  = 0.006; 128.3 mmHgvs 132.9 mmHg, P  = 0.019, respectively). Time-rate index, SD and CV of SBP, were higher in high variability group (P  < 0.001;P  < 0.001 andP  = 0.003, respectively). Time-rate index was not independently associated with the echocardiography's variables in multiple linear model when adjusting for age, 24 h-ABPM, diabetes duration and HbA1c. The multiple linear regression model revealed that the significant and independent determinants for septum thickness, relative wall thickness and posterior wall thickness (parameters of left ventricular hypertrophy) were: age (p  = 0.025;p  = 0.010;p  = 0.032, respectively) and 24 h-SBP (p  < 0.001 in the three parameters). Conclusion BP variability estimated by 24 h-ABPM is not independently associated with echocardiographic parameters in diabetic-hypertensive patients.